IMPLEMENTASI SURAT IZIN MENGEMUDI (SIM) ONLINE DAN PROSPEK MASA DEPAN - Fierda Nurany; Muhammad Arsy Nur Faizi; Pipit Widia Ningsih; Zarra Chanizka Irreza Sapna Putri; Maharani Ika Setiawati (P3M STISIPOL Dharma Wacana Metro, 2022)
The purpose of this study was to determine the implementation and future prospects of the Surabaya e-SIM application. E-SIM or electronic SIM Surabaya is an online Driving License (SIM) service innovation organized by the Colombo Surabaya SIM Administration Administration Unit (SATPAS). Through this application, residents of Surabaya and outside Surabaya are facilitated in terms of obtaining a driving license (SIM). The implementation of the Surabaya e-SIM application uses the policy implementation model of George C. Edward III by focusing on four indicators, namely communication, resources, disposition, and bureaucratic structure. The results of the study indicate the successful implementation of the e-SIM application which is shown through: 1) Communication, the Surabaya Traffic Police Satpas Satpas have carried out socialization regarding the mechanisms and procedures for using Surabaya's e-SIM. 2) Resources, the parties involved in the implementation of the SIM making program through the Surabaya e-SIM application are all levels of the Surabaya Police Satpas Satpas. 3) Disposition, the service provided is good and the community is very enthusiastic in implementing the program, each unit has its own task, it makes it easier to manage. 4) Structure, implementation of e-SIM Surabaya based on Perkap No. 9 of 2012 and SOP SIM Online. The implementation of the Surabaya e-SIM application is very influential on future prospects, namely it can facilitate public services, minimize the practice of mall administration.